PERSEPSI ETIS MAHASISWA AKUNTANSI MENGENAI SKANDAL ETIS AUDITOR DAN CORPORATE MANAGER - Himmah, Elok Faiqoh (Jurnal Akuntansi Multiparadigma, 2013)
Abstract. Studentâs Ethical Perspective on Auditorâs Ethics Scandal and Corporate Manager. The purpose of this study is to obtain empirical evidence about the influence of ethical orientation (idealism and relativism), gender and level of knowledge of the accounting studentâs perceptions regarding ethical scandals by accountant and corporate managers with research model developed by Comunale et al (2006). Results of the analysis in this study indicated that idealism, gender and level of knowledge of the public accounting profession and accounting scandals accounting affected studentâs perceptions of the ethical scandals auditors and corporate manager. On the other hand, relativism variables had no effect on accountingÂ students perceptions regarding ethical scandals auditors and corporateÂ manager.Abstrak. Persepsi Etis Mahasiswa Akuntansi Mengenai Skandal Etis Auditor Dan Corporate Manager. Tujuan penelitian ini adalah untuk mendapatkan bukti empiris mengenai pengaruh orientasi etis (idealisme dan relativisme), gender, dan tingkat pengetahuan terhadap persepsi mahasiswa akuntansi mengenai skandal etis auditor dan corporate manager dengan model penelitian yang dikembangkan oleh Comunale et al (2006). Hasil analisis dalam penelitian ini menunjukkan bahwa idealisme, gender, dan tingkat pengetahuan tentang profesi akuntan publik dan skandal akuntansi berpengaruh terhadap persepsi mahasiswa akuntansi mengenai skandal etis auditor dan corporate manager. Sedangkan, variabel relativisme berpengaruh terhadap persepsi mahasiswa akuntansi mengenai skandal etis auditor dan corporate manager.